2018
DOI: 10.1016/j.molmet.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the glucagon receptor gene before and after experimental diabetes reveals differential protection from hyperglycemia

Abstract: ObjectiveMice with congenital loss of the glucagon receptor gene (Gcgr−/− mice) remain normoglycemic in insulinopenic conditions, suggesting that unopposed glucagon action is the driving force for hyperglycemia in Type-1 Diabetes Mellitus (T1DM). However, chronic loss of GCGR results in a neomorphic phenotype that includes hormonal signals with hypoglycemic activity. We combined temporally-controlled GCGR deletion with pharmacological treatments to dissect the direct contribution of GCGR signaling to glucose c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Previous reports showed that liver-specific knockdown of GCGR resulted in decreased fasting glucose, improved insulin sensitivity, and glucose tolerance in both chow diet and high fat dietfed mice (30,31). These results further suggest that GCGR may serve as a potential target for glycemic control.…”
Section: Gcgr Predator: From Antibody To Ligandssupporting
confidence: 56%
See 1 more Smart Citation
“…Previous reports showed that liver-specific knockdown of GCGR resulted in decreased fasting glucose, improved insulin sensitivity, and glucose tolerance in both chow diet and high fat dietfed mice (30,31). These results further suggest that GCGR may serve as a potential target for glycemic control.…”
Section: Gcgr Predator: From Antibody To Ligandssupporting
confidence: 56%
“…Hence, we introduced ligand-receptor-specific interactions to further broaden the selection of targeting modules of the Predator system. Also, we selected the GCGR, a target of great potential for therapeutic usage (29)(30)(31)(32), to demonstrate that the clinically-used adenoviral vectors can be used for the delivery and functioning of the Predator system, our results showed that GCGR functioned well in primary hepatocytes. Though preliminary, these results demonstrate the clinical potential of the Predator system.…”
Section: Discussionmentioning
confidence: 99%
“…We sought to test the importance of α to β cell communication by generating a mouse line with a β cellspecific deletion of the Gcgr (Gcgr βcell-/mice; Supplemental Figure 1A; supplemental material available online with this article; https://doi.org/10.1172/jci.insight.126742DS1) (21). Islets isolated from littermate controls and Gcgr βcell-/mice perifused with graded doses of glucagon displayed identical insulin secretion profiles ( Figure 1A), suggesting that the Gcgr is dispensable for glucagon-stimulated insulin secretion.…”
Section: Resultsmentioning
confidence: 99%
“…Mice were housed under a 12-hour light/dark cycle and provided free access to a normal chow diet. Mice harboring LoxP sites in the Gcgr allele (Gcgr fl ) (21,47) were crossed with MIPcreERT (MIP-Cre) mice (48) to generate β cell-specific deletion of Gcgr (Gcgr βcell-/-). Briefly, MIP-Cre Cre/+ :Gcgr fl/fl mice were bred with MIP-Cre +/+ :Gcgr fl/fl mice to produce MIP-Cre Cre/+ :Gcgr fl/fl mice that were evenly divided to receive either oil (control) or tamoxifen (Gcgr βcell-/-).…”
Section: Methodsmentioning
confidence: 99%
“…Whether this is a mechanism that can account for the glucose lowering response to GRA therapy has not been formally tested. However, a number of studies have demonstrated that the glucose lowering in response to a GRA or following genetic deletion of the glucagon receptor (GCGR) are severely diminished in the absence of GLP-1R signaling (44,(46)(47)(48). Moreover, pharmacological or genetic elimination of glucagon action requires some level of endogenous -cell function in order to lower glycemia (49).…”
Section: Alpha Cell Hyperplasia: Metabolic Adaptation Versus Pathomentioning
confidence: 99%